The denial of labor identity as the educational principle: a deep look on the historical sense of work before capital policy (Research, Society and Development, 2019)
Work is something inherent in man, and historically fundamental to human development and survival. About everything; beyond survival, work is something that naturally produces and aggregates knowledge and knowledge. And it is in this sense that work has gained an educational identity. However, this educational identity of work is being restructured in the face of the changes brought about by technological innovations, globalization, internationalization of capital and how society is being built and modified to meet the demands of capitalism's growth. The present research aims at unleashing an understanding and revealing how capitalism has been restructured and causing intense changes in the structure of work, especially in its essence and its educational identity. This study was developed through a bibliographical survey developed in a qualitative way, through the bibliography of some important authors for the subject such as Saviani (2007), Engels (2013), Taddei (2014) and Antunes (2007). It is concluded that work has acquired an increasingly alienated identity; acquiring a reductionist and poor sense that is summarized in the form of employment, functions and professional exercises. Step by step work has been losing its meaning and identity. And thus causing a real denial of work as a creative and inherent activity of being.